Răspuns :
a) x(x+2)-13=(x-3)(x+3) <=> x^2+2x-13=x^2-9 <=> x^2-x^2+2x-13+9=0 <=> 2x-4=0 <=> 2x=4 => x=4/2 => x=2 => S={2}.
b) 4x(x-1)=(2x+5)+1 <=> 4x^2-4x=(2x+5)+1 <=> 4x^2-4x-2x-5-1=0 <=>
4x^2-6x-6=0|:2 => 2x^2-3x-3=0.
Aflam Delta=b^2-4ac => Delta= 9+24=>Delta=33>0 => => x1#x2 =(-b +/- radical din Delta)/2a
Apoi calculezi x1 si x2 inlocuind valorile in formula de mai sus.
b) 4x(x-1)=(2x+5)+1 <=> 4x^2-4x=(2x+5)+1 <=> 4x^2-4x-2x-5-1=0 <=>
4x^2-6x-6=0|:2 => 2x^2-3x-3=0.
Aflam Delta=b^2-4ac => Delta= 9+24=>Delta=33>0 => => x1#x2 =(-b +/- radical din Delta)/2a
Apoi calculezi x1 si x2 inlocuind valorile in formula de mai sus.